Anti-caking agent effects on the properties of spray-dried ‘Cempedak’ fruit powder - Pui, Liew Phing; Karim, Roselina; Yusof, Yus Aniza; Wong, Chen Wai; Mohd Ghazali, Hasanah (Universiti Putra Malaysia Press, 2020)
‘Cempedak’ fruit, an aromatic fruit that has a short shelf life can be converted into powder through spray-drying process. However, the spray-dried powder that was obtained had a high tendency to cake. Hence, three different anti-caking agents (calcium silicate, silicon dioxide, and calcium phosphate) were added separately at a concentration of 1.5% (w/w). It was found that calcium phosphate (1.5% w/w) yielded ‘cempedak’ fruit powder with lowest moisture content, water activity, hygroscopicity, and caking (change in cake height ratio), with minimal color changes in its reconstituted form and low viscosity. Different calcium phosphate concentration (0-2.00% w/w) was then applied in the production of ‘spray-dried’ powder. With increase of calcium phosphate addition from 0 to 0.66%, the moisture content, water activity, hygroscopicity, cake height ratio of ‘cempedak’ powder decreased, with no significant decrease with further addition. Calcium phosphate (0.66 % w/w) yielded powder with the best properties: lowest moisture content (4.65%), water activity (0.18), hygroscopicity (22.0), and change in cake height ratio (0.17). In addition, there was a minimal change in color of its reconstituted powder, with a slight change in viscosity.